The Role of AI in Epigenetic Analysis: A New Frontier in Medicine - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Epigenetics, the study of heritable changes in gene expression that do not involve alterations to the underlying DNA sequence, is a rapidly growing field wit...
Keywords: Precision Medicine and Genomics; Epigenetic; Analysis; Frontier; Artificial Intelligence; Machine Learning; Deep Learning